2021
DOI: 10.1093/jhps/hnab073
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Dutch version of the Hip Outcome Score; validity, reliability, and responsiveness in patients with femoroacetabular impingement syndrome

Abstract: Due to a lack of a validated Dutch version of the Hip Outcome Score (HOS) considering functional outcome after hip arthroscopy for femoroacetabular impingement syndrome, we validated the Dutch version of the HOS (HOS-NL) in patients with femoroacetabular impingement syndrome for reliability, internal consistency, construct- and content validity. Furthermore, the smallest detectable change (SDC) and minimal clinically important difference (MCID) were determined. All consecutive patients scheduled for an arthros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…For instance, in the evaluation of time at 12 months, the effect of the intervention in the arthroscopy group was observed 2 months earlier than in the physiotherapy group. Griffin et al 26 reported a difference of 85 days, almost 3 months 19 . This difference in treatment initiation time could have led to differences in the progression of the condition, severity of symptoms, and efficacy of interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in the evaluation of time at 12 months, the effect of the intervention in the arthroscopy group was observed 2 months earlier than in the physiotherapy group. Griffin et al 26 reported a difference of 85 days, almost 3 months 19 . This difference in treatment initiation time could have led to differences in the progression of the condition, severity of symptoms, and efficacy of interventions.…”
Section: Discussionmentioning
confidence: 99%
“…The minimal clinically important difference (MCID) was included in the outcomes, based on previous studies that analyzed these scales. The MCID for iHOT-33, HOS ADL, and HOS S were six, 14, and 11 points, respectively 18 , 19 . We then assessed whether MCID was achieved using the confidence intervals of the mean difference between the experimental and control groups (yes/no).…”
Section: Methodsmentioning
confidence: 95%
“…Minimally clinical important difference (MCID) was included in the outcomes based on previous studies analyzing these scales. The MCID for iHOT-33, HOS ADL, and HOS S were six, 14, and 11 points, respectively 11,12 . Then it was assessed whether MCID was achieved through the con dence intervals of the mean difference between experimental and control groups (yes/no).…”
Section: Methodsmentioning
confidence: 96%